Evolution of mate-finding Allee effect in prey - Berec, Luděk; Bernhauerová, Veronika; Boldin, Barbara (Journal of theoretical biology, 2018)
The search for mates is often accompanied with conspicuous behaviour or morphology that can be exploited by predators. Here we explore the evolutionary consequences of a trade-off that arises naturally between mate acquisition and risk of predation and study evolution of the rate at which male prey search for mates in a population subject to a mate-finding Allee effect and exposed to either generalist or specialist predators. Since we show that the mate search rate determines the strength of the mate-finding Allee effect, we can alternatively view this as evolution of the mate-finding Allee effect in prey. We contrast two different life histories and find that, predominantly, male prey either evolve towards the maximal mate search rate yielding the weakest possible mate-finding Allee effect (thus showing no adaptive response in mating behaviour to predation risk) or evolutionary bi-stability occurs. In the latter case, males evolve a relatively low mate search rate (hence a relatively strong mate-finding Allee effect, interpreted as an adaptive response of male prey to predation) when initially slow or the maximal mate search rate when initially fast. Disruptive selection does not occur in populations exposed to generalist predators but is possible when predators are specialists. The dimorphic phase, in which fast and conspicuous male prey coexist with slow and cryptic ones, is however but a transient in evolutionary dynamics as one branch goes extinct while the other evolves towards the maximal mate search rate.
Keywords: algoritmy; Biological Evolution; Female; kompetitivní chování; Animals; biologická evoluce; predátorské chování; Algorithms; mužské pohlaví; Competitive Behavior; Reproduction; Sexual Behavior, Animal; rozmnožování; zvířata; Predatory Behavior; Models, Biological; ženské pohlaví; biologické modely; sexuální chování zvířat; Male